Lanthanides - Awwad, Nasser S.; Mubarak, Ahmed T. (IntechOpen, 2019)
This edited book Lanthanides is a collection of research chapters, offering an excellent review of recent applications in our lives. It consists of a number of interesting chapters by scientists and researchers from different parts of the world. The book is divided into six chapters. The first chapter is a short introduction that explains the nature and purpose of the book and the logic and significance of its contents. In the second chapter, Katarzyna Kiegiel et al. introduce novel apparatus solutions, for example membrane contactors in the extraction stage and different types of matrices (uranium ore, phosphorites, etc.). The third chapter by Dariusz Sala and Bogus?aw Bieda from AGH University of Science and Technology, Management Department, Poland, describes the development of the life cycle inventory to rare earth elements (REEs) based on secondary sources, conducted according to ISO 14040 (2006) guidelines. Chapter 4 concentrates on lanthanide soil chemistry and shows how the soil chemistry of REEs may support soil science investigations. Dmitry V. Ladonin in Chapter 5 studies the content of forms of lanthanides in soddy-calcareous soils at different distances from the Cherepovets steel mill (Vologda region, Russia). The author concludes that the individual properties of lanthanides are clearly manifested in their interaction with soil components. The largest part of the fraction, bound to organic matter, contains medium lanthanides, while the heavy lanthanides are bound to Fe and Mn (hydr)oxides. The last chapter discusses ecological and physiological impacts of lanthanides on algae as primary producers in aquatic environments. This book will definitely encourage readers, researchers, and scientists to look further into the frontier topics of lanthanides and opens new possible research paths for further novel development.